Does stakeholder pressure drive carbon emission disclosure? evidence from the mining and energy sector in Indonesia - Sulistiyanti, Umi; Setiawan, Doddy; Aryani, Y. Anni; Hartoko, Sri (Proceeding International Conference on Accounting and Finance, 2026)
This study examines the influence of media exposure, government pressure and institutional investors on carbon disclosure of mining and energy companies in Indonesia. The sample consists of 235 firm-year observations from 47 mining and energy companies in Indonesia. This study uses annual reports and sustainability reports covering the period from 2017 to 2021 as data sources. The collected data were analyzed using multiple regression with the Ordinary Least Squares (OLS) method. These findings indicate that institutional investors positively affect carbon disclosure as opposed to the negative and significant impact induced by the government. Meanwhile, media exposure has no significant relationship on carbon disclosure. The results of this study underscore the critical role of external stakeholders in fostering corporate accountability and transparency, particularly with regard to carbon emissions disclosure. This study considers the large segments of companies in developing countries like Indonesia which is also the top contributor of carbon emissions in Southeast Asia, meanwhile previous research focused on countries with developed economies.